Gas phase synthesis of dimethyl carbonate from CO2 and CH3OH over Cu-Ni/AC. A kinetic study (2020)
ABSTRACT : The catalytic activity for dimethyl carbonate formation from carbon dioxide and methanol over mono and bimetallic Cu:Ni supported on activated carbon is presented. Bimetallic catalysts exhibit higher catalytic activity than the monometallic samples, being Cu:Ni-2:1 (molar ratio) the best catalyst; X-Ray diffraction, transmission electron microscopy, and metal dispersion analysis provided insight into the improved activity. In situ FT-IR experiments were conducted to investigate the mechanism of formation of dimethyl carbonate from methanol and carbon dioxide over Cu-Ni:2-1. The kinetics of the direct synthesis of dimethyl carbonate in gas phase over Cu:Ni-2:1 supported on activated carbon catalyst was experimentally investigated at 12 bar and temperatures between 90 oC and 130 oC, varying the partial pressures of CO2 and methanol. Experimental kinetic data were consistent with a Langmuir–Hinshelwood model that included carbon dioxide and methanol adsorption on catalyst actives sites (Cu, Ni and Cu-Ni), and the reaction of adsorbed CO2 with methoxi species as the rate determining step. The estimated apparent activation energy was 94.2 kJ mol-1.